Mesenchymal Stem Cell Secretome Enhancement by Nicotinamide and Vasoactive Intestinal Peptide: A New Therapeutic Approach for Retinal Degenerative Diseases. (27th June 2020) - Alonso-Alonso, Maria L.; Srivastava, Girish K.; Usategui-Martín, Ricardo; García-Gutierrez, Maria T.; Pastor, José Carlos; Fernandez-Bueno, Ivan
Abstract : Mesenchymal stem cells (MSC) secrete neuroprotective molecules that may be useful as an alternative to cell transplantation itself. Our purpose was to develop different pharmaceutical compositions based on conditioned medium (CM) of adipose MSC (aMSC) stimulated by and/or combined with nicotinamide (NIC), vasoactive intestinal peptide (VIP), or both factors; and to evaluate in vitro their proliferative and neuroprotective potential. Nine pharmaceutical compositions were developed from 3 experimental approaches: (1) unstimulated aMSC-CM collected and combined with NIC, VIP, or both factors (NIC+VIP), referred to as the aMSC-CM combined composition; (2) aMSC-CM collected just after stimulation with the mentioned factors and containing them, referred to as the aMSC-CM stimulated-combined composition; and (3) aMSC-CM previously stimulated with the factors, referred to as the aMSC stimulated composition. The potential of the pharmaceutical compositions to increase cell proliferation under oxidative stress and neuroprotection were evaluated in vitro by using a subacute oxidative stress model of retinal pigment epithelium cells (line ARPE-19) and spontaneous degenerative neuroretina model. Results showed that oxidatively stressed ARPE-19 cells exposed to aMSC-CM stimulated and stimulated-combined with NIC or NIC+VIP tended to have better recovery from the oxidative stress status. Neuroretinal explants cultured with aMSC-CM stimulated-combined with NIC+VIP had better preservation of the neuroretinal morphology, mainly photoreceptors, and a lower degree of glial cell activation. In conclusion, aMSC-CM stimulated-combined with NIC+VIP contributed to improving the proliferative and neuroprotective properties of the aMSC secretome. Further studies are necessary to evaluate higher concentrations of the drugs and to characterize specifically the aMSC-secreted factors related to neuroprotection. However, this study supports the possibility of improving the potential of new effective pharmaceutical compositions based on the secretome of MSC plus exogenous factors or drugs without the need to inject cells into the eye, which can be very useful in retinal pathologies.